THE CHASTUSHKA AND THE LAPAR AS GENRES OF VERBAL COMPETITION: TYPOLOGY, POETICS, AND LINGUOCULTURAL PARALLELS - Кодиров Алижон Нуралиевич (Bright Mind Publishing, 2025)
The article examines the Russian chastushka and the Uzbek lapar as folklore genres based on verbal competition and improvisation. The aim of the study is to identify typological similarities and differences between these genres in terms of poetics, composition, linguistic means, and social functions. The research is conducted within linguocultural and comparative-typological frameworks. The study concludes that despite their national specificity, chastushka and lapar share common mechanisms of folk dialogue, competitiveness, and collective reflection.
Keywords: Chastushka, lapar, folklore, verbal contest, linguoculture, improvisation, poetics, small genres.